El cuerpo social o el síntoma contemporáneo - Nelson Cortés Castaño (Universidad de Antioquia, 2001)
There is an endless cult in the contemporary world for a young and beautiful human body, furthermore, to also avoid getting old. It is a cultural symptom that has increased the indisposition of humans that feel trapped by marketing and forced to consume its products. We are facing a social symptom that arises in the measure in which the Individual is subjected to this contemporary master, to a marketing that homogenizes and excludes the singular, that excludes his/her own particularity which makes the subject desirable. Modern man is then obligated to reflect the life style of a society in which the important predominance are youth and longevity, two conditions present in the so called body aesthetics, a young and athletic body, a beautiful face and bright teeth. As we can appreciate, there is a new and large offer of dental services- limited in the past to an almost exclusively extraction of a damaged tooth-, now a days it includes from the replacement of lost teeth to their cosmetic remodeling; services that are sought by the patient, motivated many times by the emotional conflicts that he/she has placed in their mouth.